Six new Cyrtodactylus (Squamata: Gekkonidae) from northeast India - Agarwal, Ishan; Mahony, Stephen; Giri, Varad B.; Chaitanya, R.; Bauer, Aaron M. (Zootaxa, 2018)
We use mitochondrial sequence data to identify divergent lineages within the gekkonid genus Cyrtodactylus in northeast India and use morphological data to describe six new species from within the Indo-Burma clade of Cyrtodactylus. The new species share an irregular colour pattern but differ from described species from the region in morphology and mitochondrial sequence data (>11 % uncorrected pairwise sequence divergence). Three new species are from along the Brahmaputra River and three are from mountains south of the Brahmaputra, including the largest Cyrtodactylus from India and the fifth gecko to be described from a major Indian city, Guwahati.